2007
DOI: 10.2217/14622416.8.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Interindividual Variability of Warfarin Dose Requirement in Adult Korean Patients

Abstract: In the present study, we found that the VKORC1 polymorphism had a dominant genetic influence on interindividual variability for warfarin dose in Korean patients. It explained approximately 32% of the overall variability in warfarin dose requirements given all of the variables studied. Thus, analysis of the VKORC1 genotypes may be important to guide warfarin dose selection and allow personalized warfarin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 37 publications
4
18
1
Order By: Relevance
“…The frequency of the CYP2C9 variant type was approximately 12% in other Korean studies [13,14] and was 8% in other Asians [15][16][17].…”
Section: Discussionmentioning
confidence: 81%
“…The frequency of the CYP2C9 variant type was approximately 12% in other Korean studies [13,14] and was 8% in other Asians [15][16][17].…”
Section: Discussionmentioning
confidence: 81%
“…2,4 Cho HJ et al suggested that it explained B32% of the overall variability in warfarin dose requirements given all of the variables studied in Koreans. 22 In Japanese patients, the model using the multiple regression analysis including age, sex, weight and three genetic polymorphisms accounted for 33.3% of total variations in warfarin dose. 4 Also, a multiple regression model based on the genetic polymorphisms of VKORC1, CYP2C9, EPHX1 and the non-genetic factors of age and body weight can explain 40.2% of the variance in warfarin dose in Han Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…This dependent therapeutic action of the drug linked to albumin affinity has already been reported for warfarin. Although a genetic factor has been identified in 30% of cases, the other causes of variability in the therapeutic efficiency of warfarin among patients remain unknown (14)(15)(16). In the context of diabetes, hyperglycemia…”
Section: Introductionmentioning
confidence: 99%